The Influenceof Digital Media on Improving Nursing English Language Ability at Timor University - Sefrina Maria Seuk Asa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study is a qualitative descriptive study. The researcher interviewed 15 nursing students at Timor University. In addition to using the interview method, the researcher also used literature review and observation. In the literature review, the researcher collected literature related to digital media containing English learning content. Meanwhile, in the observation, the researcher observed 15 nursing students at Timor University. The results of the study indicate that digital media has an influence on improving the English language skills of nursing students at Timor University. The advantages of digital media are lower costs, richer learning spaces, communicative, providing more specific materials, saving more time, more flexible learning time, and increasing learning motivation. This has an impact on improving the English learning skills of nursing students at Timor University.